Do firm characteristics affect environmental sustainability? A literature review‐based assessment - Balasubramanian, Sreejith; Shukla, Vinaya; Mangla, Sachin; Chanchaichujit, Janya (Business strategy and the environment, 2021)
Combating environmental pollution and climate change mandates strong commitment and participation of all firms across sectors. However, the environmental conduct of firms is seen to vary as per their characteristics, especially their size, ownership, and age. Current understanding of these characteristics' influence on environmental sustainability is limited, fragmented, and scattered across the literature, which this study seeks to improve and contribute to. Based on a rigorous screening of the last 25 years' literature (1996–2020), the study develops a comprehensive understanding of firm characteristics' implications for environmental sustainability, namely, environmental practices implementation, environmental drivers, environmental barriers, and associated (environmental, cost/economic, operational, and organizational) performance implications. Several meaningful and generalizable trends, conflicts, and consensus, or lack thereof, are revealed. For instance, the extent of environmental practices' implementation can be seen to be greater at large firms' (vis‐à‐vis small ones) and at foreign firms' (vis‐à‐vis local ones), though not much difference is seen between old and new firms. Also, several metafactors such as resources availability, innovation propensity, and bureaucracy and organizational inertia are identified that explain the differential influence of firm characteristics on environmental sustainability and dispel erroneous stereotypes. Finally, gaps in the literature offering avenues for future research are highlighted along with implications for research, theory, and practice. Results are expected to help policymakers and practitioners develop policies/interventions that ensure all firms, irrespective of their characteristics contribute to environmental sustainability. A comprehensive review of this kind has not been previously undertaken and constitutes the novelty of this work.